2010
DOI: 10.1007/s11425-010-3148-y
|View full text |Cite
|
Sign up to set email alerts
|

A specific family of cyclotomic polynomials of order three

Abstract: Let A(n) be the largest absolute value of any coefficient of n-th cyclotomic polynomial Φn(x). We say Φn(x) is flat if A(n) = 1. In this paper, for odd primes p < q < r and 2r ≡ ±1 (mod pq), we prove that Φpqr(x) is flat if and only if p = 3 and q ≡ 1 (mod 3).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…This result was generalized by Flanagan [8] and improved by Kaplan [11]. There have been also studies of Φ pqr (x) with A(pqr) = 1, see [6,7,10,16]. In [11], Kaplan established the following periodicity of the function A(pqr).…”
Section: B Zhangmentioning
confidence: 88%
“…This result was generalized by Flanagan [8] and improved by Kaplan [11]. There have been also studies of Φ pqr (x) with A(pqr) = 1, see [6,7,10,16]. In [11], Kaplan established the following periodicity of the function A(pqr).…”
Section: B Zhangmentioning
confidence: 88%
“…Kaplan (2007) [64, Lemma 1] proved the following lemma, which provides a formula for the coefficients of ternary cyclotomic polynomials. This is known as Kaplan's lemma and has been used to prove several results on ternary cyclotomic polynomials [37,48,49,51,60,89,100,101,102,105,106]. Lemma 3.1 (Kaplan's lemma).…”
Section: Ternary Cyclotomic Polynomialsmentioning
confidence: 99%
“…Ji (2010) [60] considered odd primes p < q < r such that 2r ≡ ±1 (mod pq) and showed that in such a case Φ pqr (X) is flat if and only if p = 3 and q ≡ 1 (mod 3). For a ∈ {3, 4, 5}, Zhang (2017) [102] gave similar characterizations for the odd primes such that ar ≡ ±1 (mod pq) and Φ pqr (X) is flat (see also [106] for a weaker result for the case a = 4).…”
Section: Flatnessmentioning
confidence: 99%
“…We say Φ n (x) is flat if A(n) = 1. ChunGang Ji [18] proved that if p < q < r are odd prime and 2r ≡ ±1(mod pq), then Φ pqr (x) is flat iff p = 3 and q ≡ 1(mod 3). It follows that M(p; q) ≥ 2 for p > 3.…”
Section: Lemma 14mentioning
confidence: 99%